1991
DOI: 10.1039/ft9918701733
|View full text |Cite
|
Sign up to set email alerts
|

Self-association of phenols in inert solvents. Apparent heat capacities of phenol, substituted phenols and aromatic alcohols in n-heptane

Abstract: Apparent heat capacities have been measured for phenol, substituted phenols and aromatic alcohols in dilute n-heptane at 25 "C. The alcohols are phenol, o-cresol, rn-cresol, p-cresol, 2,6-dimethylphenol, 3,5-dimethylp he no I, 3,5-d i -tert-b u ty I p he n o I, 2,6-d i-tert-b u t y I p he n o I, 2,4,6-t r i-tert-bu ty I p h e no I, 2,6-d i -tert-b u ty I -4-met h y I p hen o I, 2-te rtb u t y I p he no I, 4-te rtb u t y I p h e n o I, 2-e t h y I p h e no I , 2 -prop y I p h e no I, 2-p h en y I p h e no I, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…This is in fact what was found in ref. 4, where it was shown that benzyl alcohol has a AHo value similar to that for linear alcohols. In ref.…”
Section: Effect Of N Electronsmentioning
confidence: 91%
See 4 more Smart Citations
“…This is in fact what was found in ref. 4, where it was shown that benzyl alcohol has a AHo value similar to that for linear alcohols. In ref.…”
Section: Effect Of N Electronsmentioning
confidence: 91%
“…The results in Table 2 allow the qualitative discussion of several observations made in ref. 4 and 5 regarding the selfassociation behaviour of alcohols. For benzyl alcohol, which has an aromatic ring, but whose hydroxyl group is separated from it by a CH, group, the MNDO calculations show that the oxygen atom does not transfer electronic charge to the aromatic ring, and as a consequence it must form a strong hydrogen bond.…”
Section: Effect Of N Electronsmentioning
confidence: 93%
See 3 more Smart Citations